Alcoholic Cardiomyopathy - Ziyodullaev Maksud Maksmudovich (Research Journal of Trauma and Disability Studies, 2024)
Alcoholic-dilated Cardiomyopathy (ACM) is the most prevalent form of ethanol-induced heart damage. Ethanol induces ACM in a dose-dependent manner, independently of nutrition, vitamin, or electrolyte disturbances. It has synergistic effects with other heart risk factors. ACM produces a progressive reduction in myocardial contractility and heart chamber dilatation, leading to heart failure episodes and arrhythmias. Pathologically, ethanol induces myocytolysis, apoptosis, and necrosis of myocytes, with repair mechanisms causing hypertrophy and interstitial fibrosis. Myocyte ethanol targets include changes in membrane composition, receptors, ion channels, intracellular [Ca2+] transients, and structural proteins, and disrupt sarcomere contractility. Cardiac remodeling tries to compensate for this damage, establishing a balance between aggression and defense mechanisms. The final process of ACM is the result of dosage and individual predisposition. The ACM prognosis depends on the degree of persistent ethanol intake. Abstinence is the preferred goal, although controlled drinking may still improve cardiac function. New strategies are addressed to decrease myocyte hypertrophy and interstitial fibrosis and try to improve myocyte regeneration, minimizing ethanol-related cardiac damage. Growth factors and cardiomyokines are relevant molecules that may modify this process. Cardiac transplantation is the final measure in end-stage ACM but is limited to those subjects able to achieve abstinence.